Speed and spin characteristics of table tennis balls : a comparison of the old celluloid balls and new plastic balls - Oh, Wen-Jing (2015)
ITTF has introduced a new plastic table tennis ball (40+mm) to replace the previous celluloid ball (40mm). The purpose of this study was to investigate 1) the difference in spin and speed characteristics between the plastic and celluloid ball, and 2) its effects on the player’s technique. The study consisted of mechanical and human testing. Mechanical testing was done on the ball-feeding machine for both balls. Data collected included the ball spin, speed, and peak rebound height. Five Singapore national athletes (Age: 23.0 ± 3.8) performed fifteen trials using a forehand topspin loop drive on each ball. Speed and spin of the ball after contact with the racket was analyzed using a high speed camera (2000fps). Racket speed, racket face angle, impact height of the ball from the table, and distance of contact to the table edge were measured using 3D motion capture (500Hz). A Wilcoxon Signed Rank Test was performed on each kinematic variable collected during human trials. For the mechanical testing, spin and speed of the plastic ball was lower, and also achieved a lower peak height after rebound with the table. For the human testing, the impact height of the plastic ball from the table was found to be lower (0.02m) than the celluloid ball (p = .043). No significant differences were found between the other kinematic variables. All participants indicared that using more strength for the plastic ball is required, and one participant felt that contact with the plastic ball had to be closer to the table edge.